2021
DOI: 10.1248/bpb.b21-00054
|View full text |Cite
|
Sign up to set email alerts
|

NSC23766 and Ehop016 Suppress Herpes Simplex Virus-1 Replication by Inhibiting Rac1 Activity

Abstract: Herpes simplex virus-1 (HSV-1) infection of the eyes leads to herpes simplex virus keratitis (HSK), the main cause of infectious blindness in the world. As the current therapeutics for HSV-1 infection are rather limited and prolonged use of acyclovir (ACV)/ganciclovir (GCV) and in immunocompromised patients lead to the rise of drug resistant mutants, it underlines the urgent need for new antiviral agents with distinct mechanisms. Our study attempted to establish ras-related C3 botulinum toxin substrate 1 (Rac1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Graber et al and our present study published in the Biological and Pharmaceutical Bulletin showed that HSV-1 infection upregulated Rac1 activity to support its replication ( 35 , 36 ). In addition, a previous study has shown that 6-TG mediated immunosuppressive effects by interfering with Rac1 protein function ( 20 ).…”
Section: Resultssupporting
confidence: 57%
“…Graber et al and our present study published in the Biological and Pharmaceutical Bulletin showed that HSV-1 infection upregulated Rac1 activity to support its replication ( 35 , 36 ). In addition, a previous study has shown that 6-TG mediated immunosuppressive effects by interfering with Rac1 protein function ( 20 ).…”
Section: Resultssupporting
confidence: 57%
“…When determining the effectiveness of the proposed interventions, five (3.65%) were shown not to be effective [84,107,126,131,139], three (2.19%) were somewhat effective [21,46,53], and 128 (93.43%) were effective as potential managements for resistant strains of HSV [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][47][48][49][50][51][52][54][55][56][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]…”
Section: Data Extractionmentioning
confidence: 99%
“…Harringtonine is a natural alkaloid and homolog which exhibits antitumor activities, giving for its use in leukemia. Its mechanism of action is that it blocks peptide bond formation and aminoacyl-tRNA binding, ultimately preventing protein synthesis ( Table 3 ) [ 108 ]. More recently, its antiviral effects have been recognized, particularly against chikungunya virus [ 109 ], Singapore grouper iridovirus [ 110 ], varicella-zoster virus [ 111 ], and Zika virus [ 112 ].…”
Section: Clinical Management Of Hsv Keratitismentioning
confidence: 99%
“…This was accomplished by harringtonine’s ability to suppress the herpes virus entry mediator expression, thus preventing viral entry of HSV-1 [ 9 ]. Finally, in 2021, Zhang et al found that Ras-related C3 botulinum toxin substrate 1 could be a novel therapeutic target against HSV-1 [ 108 ].…”
Section: Clinical Management Of Hsv Keratitismentioning
confidence: 99%